Hybrid in silico/in vitro target fishing to assign function to “orphan” compounds of food origin – The case of the fungal metabolite atromentin - Dellafiora, Luca; Aichinger, Georg; Geib, Elena; Sánchez-Barrionuevo, Leyre; Brock, Matthias; Cánovas, David; Dall'Asta, Chiara; Marko, Doris (Elsevier, 2019)
Many small molecules of food origin may effect human health but lack an adequate description of their biological activity. To fill this knowledge gap, a first-line workflow is needed to assign putative functions, rank the endpoints for testing and guide wet-lab experiments. In this framework, the identification of potential biological targets can be used to probe the activity of orphan compounds using a so-called “target fishing” approach. Here, we present a proof of concept study using an in silico/in vitro target fishing approach on the fungal secondary metabolite atromentin. The procedure relies on a computational screening for activity identification coupled with experimental trials for dose-response characterization. Computational results identified estrogen receptors and 17-β-hydroxysteroid dehydrogenase as potential targets. Experiments confirmed a weak estrogenic activity, supporting the reliability of the procedure. Despite limited estrogenicity of atromentin, the proposed inhibition of 17-β-hydroxysteroid dehydrogenase should be considered as a source for endocrine disruptive effects.